LENGTH-WEIGHT RELATIONSHIP OF CLARIAS GARIEPINUS FED PSIDIUM GUAJAVA AND MANGIFERA INDICA LEAF EXTRACT - Ekpemikoghene, Ikenga Esther; Arimiche, Nwabueze Agatha; Kesena, Ekelemu Jerimoth (FUDMA Journal of Sciences, 2024)
The length weight relationship (LWR) of Clarias gariepinus fed Psidium guajava and Mangifera indica leaf extract was evaluated for six (6) months. A total of 420, eight (8) weeks old fingerlings of Clarias gariepinus was used for this study. Experimental fish were fed 40 % crude protein diet with inclusion of both leaf extracts at 0 %, 4 %, 6 %, and 8 %. Experimental fish were stocked in twenty-one 4ft by 4ft tarpaulin tanks half filled with borehole water, acclimation was done for 7 days during which they were fed commercial diet. Aqueous extract was done for both leaves and stored in plastic cans for further use. Weight and length of fish was measured biweekly and data was used to assess the length-weight relationship. The result of this study showed that the best weight was recorded in treatment 2 fed 4 % Psidium guajava extract and the least in treatment 5 fed 4 % Mangifera indica extract. The result on LWR revealed the regression coefficient ‘b’ to be from 17.68-20.40 which indicates a positive allometric growth, since ‘b’ value is more than 3. This further means that the fish samples in this study became heavier, stouter, deeper bodied or bigger as it increases in length i.e all parts of the fish increase in size proportionately with the length.